Blood Pressure Goals and Clinical Outcomes after Successful Endovascular Therapy: A Multicenter Study. Issue 6 (3rd April 2020) - Anadani, Mohammad; Arthur, Adam S.; Tsivgoulis, Georgios; Simpson, Kit N.; Alawieh, Ali; Orabi, Yser; Goyal, Nitin; Alexandrov, Andrei V.; Maier, Ilko L.; Psychogios, Marios‐Nikos; Liman, Jan; Brinton, Daniel; et al.
Abstract : Objective: Elevated systolic blood pressure (SBP) after successful revascularization (SR) via endovascular therapy (EVT) is a known predictor of poor outcome. However, the optimal SBP goal following EVT is still unknown. Our objective was to compare functional and safety outcomes between different SBP goals after EVT with SR. Methods: This international multicenter study included 8 comprehensive stroke centers and patients with anterior circulation large vessel occlusion who were treated with EVT and achieved SR. SR was defined as modified thrombolysis in cerebral ischemia 2b to 3. Patients were divided into 3 groups based on SBP goal in the first 24 hours after EVT. Inverse probability of treatment weighting (IPTW) propensity analysis was used to assess the effect of different SBP goals on clinical outcomes. Results: A total of 1, 019 patients were included. On IPTW analysis, the SBP goal of <140mmHg was associated with a higher likelihood of good functional outcome and lower odds of hemicraniectomy compared to SBP goal of <180mmHg. Similarly, SBP goal of <160mmHg was associated with lower odds of mortality compared to SBP goal of <180mmHg. In subgroup analysis including only patients with pre‐EVT SBP of ≥140mmHg, an SBP of <140mmHg was associated with a higher likelihood of good functional outcome, lower odds of symptomatic intracranial hemorrhage, and lower odds of requirement for hemicraniectomy compared to SBP goal of <180mmHg. Interpretation: SBP goals of <140 and < 160mmHg following SR with EVT appear to be associated with better clinical outcomes than SBP of <180mmHg. ANN NEUROL 2020;87:830–839